Evaluating Human Patient Simulation Fidelity and Effectiveness for Combat-Medical Training. Issue 1 (September 2019) - Winner, Jennifer; Millwater, Teresa L.
Two leading causes of survivable combat deaths are hemorrhage and airway compromise. Although individual medical-training competency requirements are met using human-patient simulation (HPS), the evaluation of fidelity and HPS impact on training outcomes are not well documented. Research has documented physical fidelity concerns when comparing human anatomy to simulators, but has largely overlooked informational needs such as visual, auditory, and tactile cues for patient assessment. Training impact is often characterized by changes in confidence; however, the Dunning-Kruger effect suggests that overconfidence is pervasive. The purpose of this paper is to provide perspective on the research needs to ensure human-patient simulation meets the requirements for combat-medic training.